Disinfection by hydrogen peroxide nebulization increases susceptibility to avian pathogenic Escherichia coli. (December 2015) - Oosterik, Leon; Tuntufye, Huruma; Janssens, Steven; Butaye, Patrick; Goddeeris, Bruno
Abstract Background Avian pathogenicEscherichia coli (APEC) are the major cause of economic losses in the poultry industry worldwide. Traditionally, antibiotics are used to treat and prevent colibacillosis in broilers. Due to resistance development other ways of preventing/treating the disease have to be found. Therefore during this study the nebulization of low concentrations of hydrogen peroxide (H2 O2 ) was tested in the presence of chickens to lower pathogenicity of APEC. Results Significantly higher total lesion scores and higherE. coli concentrations were found in the spleen of chickens exposed to 2 % H2 O2 compared to those exposed to 1 % H2 O2 and control chickens which had been exposed to nebulization with distilled water. Higher total lesions scores andE. coli concentrations in the spleen were found in chickens exposed to 1 % H2 O2 in comparison to control chickens (not significant). Conclusion H2 O2 is rendering animals more prone to APEC infection contraindicating H2 O2 nebulization in the presence of chickens.